If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 16x + -4y Solving 12 = 16x + -4y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 12 + -16x = 16x + -16x + -4y Combine like terms: 16x + -16x = 0 12 + -16x = 0 + -4y 12 + -16x = -4y Add '-12' to each side of the equation. 12 + -12 + -16x = -12 + -4y Combine like terms: 12 + -12 = 0 0 + -16x = -12 + -4y -16x = -12 + -4y Divide each side by '-16'. x = 0.75 + 0.25y Simplifying x = 0.75 + 0.25y
| 1.5c+8.1=-23.25 | | 3x+6x-4=50 | | m-4+10=2m-5 | | 20x+5-7x=15 | | a/-2=2.5-3a | | 2(x+2)+5=5x-3(-4+x) | | 2m-mn= | | k./.5+7=10 | | 4x+10y=300.000 | | lg(8x+3)=1 | | 2(x-3)+5=-4(2x-1) | | 3-4(x-5)=3x+6(x-3) | | R+48=7c | | Q=7-2p | | 10=4d+2 | | 2.4x+7.2=-62.4 | | 2(-5)-3(3/4)-(6) | | 2lx-6l=48 | | f(x)=x^4-3x^2+5 | | 25x+2y-19x-1y= | | 4x^2+25y^2-50y=75 | | -7.9d+7.7=274.72 | | (-5)(6)(1/3) | | -7d+7.7=274.72 | | 5p-2=3/4 | | -3(x-1)+9=3 | | 5+3h=17 | | (2x-3)+5=-4(2x-1) | | n+23445566776554544=23445566776554544 | | m/-3=2 | | -u+9=32.9 | | T-(-1)=(-5) |